Orthotopic liver transplantation in an adult withsitus inversus : an easy way to fit the liver (2006)
ABSTRACT: Situs inversus (SI) is a rare congenital disorder with acomplete mirror image of thoracic and abdominal or-gans. In adults with SI and decompensated cirrhosis ex-perience with liver transplantation is limited. Orthoto-pic liver transplantation (OLT) in an adult with cirrho-sis using a technique where the recipient liver wasplaced using a 90-degree rotation of the graft was previ-ously reported by Klintmalm et al, however no other re-ports using this technique have been described. We re-port a case of a 41 year-old man with situs inversus anddecompensated cirrhosis who successfully underwentOLT using this technique. The donor liver was rotated90-degrees towards the left and easily fitted into the re-cipients’ fossa with the left lobe pointing toward the leftlower quadrant. The patient had an uneventful recoveryand has been followed for 21 months without any com-plications. This technique has the advantage of prevent-ing compromise of the size of the donor liver, permits aneasy reconstruction of vascular and biliary tree and inthis case was associated with an excellent outcome